Osh6 Revisited: Control of PS Transport by the Concerted Actions of PI4P and Sac1 Phosphatase - Eisenreichova, Andrea; Różycki, Bartosz; Boura, Evzen; Humpolickova, Jana (Frontiers in Molecular Biosciences, 2021)
Osh6, a member of the oxysterol-binding protein–related protein (ORP) family, is a lipid transport protein that is involved in the transport of phosphatidylserine (PS) between the endoplasmic reticulum (ER) and the plasma membrane (PM). We used a biophysical approach to characterize its transport mechanism in detail. We examined the transport of all potential ligands of Osh6. PI4P and PS are the best described lipid cargo molecules; in addition, we showed that PIP2 can be transported by Osh6 as well. So far, it was the exchange between the two cargo molecules, PS and PI4P, in the lipid-binding pocket of Osh6 that was considered an essential driving force for the PS transport. However, we showed that Osh6 can efficiently transport PS along the gradient without the help of PI4P and that PI4P inhibits the PS transport along its gradient. This observation highlights that the exchange between PS and PI4P is indeed crucial, but PI4P bound to the protein rather than intensifying the PS transport suppresses it. We considered this to be important for the transport directionality as it prevents PS from returning back from the PM where its concentration is high to the ER where it is synthesized. Our results also highlighted the importance of the ER resident Sac1 phosphatase that enables the PS transport and ensures its directionality by PI4P consumption. Furthermore, we showed that the Sac1 activity is regulated by the negative charge of the membrane that can be provided by PS or PI anions in the case of the ER membrane.